Share and care - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The World of Spore Readers (2:10) . Summary report of the Uses of Spore Survey readers quotation Share and care Each time I read something very special in Spore, I pass on the information to neighbouring farmers who cannot read. I even organised...